Sugar transporters of the SWEET family and their role in arbuscular mycorrhiza - A. A. Kryukov; A. O. Gorbunova; T. R. Kudriashova; O. I. Yakhin; A. A. Lubyanov; U. M. Malikov; M. F. Shishova; A. P. Kozhemyakov; A. P. Yurkov (Вавиловский журнал генетики и селекции)
Plant sugar transporters play an essential role in the organism’s productivity by carrying out carbohydrate transportation from source cells in the leaves to sink cells in the cortex. In addition, they aid in the regulation of a substantial part of the exchange of nutrients with microorganisms in the rhizosphere (bacteria and fungi), an activity essential to the formation of symbiotic relationships. This review pays special attention to carbohydrate nutrition during the development of arbuscular mycorrhiza (AM), a symbiosis of plants with fungi from the Glomeromycotina subdivision. This relationship results in the host plant receiving micronutrients from the mycosymbiont, mainly phosphorus, and the fungus receiving carbon assimilation products in return. While the efficient nutrient transport pathways in AM symbiosis are yet to be discovered, SWEET sugar transporters are one of the three key families of plant carbohydrate transporters. Specific AM symbiosis transporters can be identified among the SWEET proteins. The survey provides data on the study history, structure and localization, phylogeny and functions of the SWEET proteins. A high variability of both the SWEET proteins themselves and their functions is noted along with the fact that the same proteins may perform different functions in different plants. A special role is given to the SWEET transporters in AM development. SWEET transporters can also play a key role in abiotic stress tolerance, thus allowing plants to adapt to adverse environmental conditions. The development of knowledge about symbiotic systems will contribute to the creation of microbial preparations for use in agriculture in the Russian Federation.